PENGGUNAAN METODE SING TO PLAY SEBAGAI ALTERNATIF PENDIDIKAN BAHASA INGGRIS YANG EFEKTIF DAN MENYENANGKAN PADA SISWA KELAS TIGA SEKOLAH DASAR DI DESA GANGIN KOTA SEMARANG - Sa’diyah, Chalimatus; Harjiyanti, Ninin; Arumsari, Aulia; Mudhofar, Ahmad; Ernayanti, Anisah Suci (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
English is the international language that is used as a communication in all activities that are International. It should be recognized that not all students understand with English, especially for elementary school students. English is considered to be one of the difficult lesson because English became the third after regional laguages and indonesian language. Teachers doesnât variety of learning methods resulted in lowboring for student spirit. Therefore increase the motivation to learn required the existence of alternative effective English learning and fun. One alternative is given by using the method âsing to playâ. This method is the singing while playing a fun to stimulate a childs brain in order to more rapid understand the lesson.